Failure of building automation system / Mohd Syamsul Khairil Mohd Supian - Mohd Supian, Mohd Syamsul Khairil (2008)
Building automation system (BAS) is a programmed, computerized and intelligent network of electronic devices to make an easier work for the staff or technician to monitor, control and operate other building services such as air conditioning, electrics, fire protection, lifts, security and plumbing system. By using the BASthe energy saving can be achieved and using less staff compare to the conventional system. Although the BAS can give benefit, but the installation of the BAS needs a high expenditure, require specialist, proper planning and maintenance for this system. But not all BAS installations are successful, because of several factors such as lack of planning, lack of maintenance and the obsolete system will contribute the BAS failure to running. This academic project will focus on the operation of the BAS, factor of successful and failure of BAS. The method of this study involved literature review, structure interview and base on the case study. This academic project will use a structure interview to collect a data and the data from the interview session will be analysis to acquire the finding. From there the operation of BAS, factor of failure for each case study will be identifying. Finally the study ends with a chapter on conclusion are provide on this topic.